Back Cover: Myo‐Inositol in Fermented Sugar Matrix Improves Human Macrophage Function. Issue 8 (19th April 2022) - Ghosh, Nandini; Das, Amitava; Biswas, Nirupam; Mahajan, Sanskruti P.; Madeshiya, Amit K.; Khanna, Savita; Sen, Chandan K.; Roy, Sashwati
Abstract : Mol. Nutr. Food Res . 2022, 66, 202100852 DOI: 10.1002/mnfr.202100852 Fermented Papaya Preparation (FPP) treatment increases macrophage intracellular myo ‐inositol. FPP and myo ‐inositol bolsters human macrophage ROS production and phagocytosis. Myo ‐inositol transporters SMIT1and HMIT are involved in FPP and myo ‐inositol induced macrophage functions. Myo ‐inositol improves macrophage functions via ISYNA1 and RAC2‐mediated pathway. This is reported by Sashwati Roy and co‐workers in article number 2100852 .